1996
DOI: 10.1091/mbc.7.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Purification and identification of FOAD-II, a cytosolic protein that regulates secretion in streptolysin-O permeabilized mast cells, as a rac/rhoGDI complex.

Abstract: Mast cells permeabilized by treatment with streptolysin-O in the presence of Ca2+ and GTP-gamma-S can secrete almost 100% of their contained N-acetyl-beta-D-glucosaminidase. If these stimuli are provided to the permeabilized cells after a delay, the response is diminished and the ability of the cells to undergo secretion runs down progressively over a period of about 30 min. This is thought to be due to the loss of key proteins involved in the exocytotic mechanism. Using this effect as the basis of a biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 53 publications
4
46
0
Order By: Relevance
“…Moreover, O'Sullivan et al (1996) have recently reported that Rac complexed with Rho GDI is involved in Ca 2þ -dependent exocytosis from permeabilized rat mast cells. In their experiments, when rat mast cells are permeabilized with streptolysin-O and immediately stimulated by GTPgS in the presence of Ca 2þ , Ca 2þ -dependent exocytosis occurs, but when stimulated after a delay, this reaction is markedly reduced.…”
Section: Figurementioning
confidence: 99%
“…Moreover, O'Sullivan et al (1996) have recently reported that Rac complexed with Rho GDI is involved in Ca 2þ -dependent exocytosis from permeabilized rat mast cells. In their experiments, when rat mast cells are permeabilized with streptolysin-O and immediately stimulated by GTPgS in the presence of Ca 2þ , Ca 2þ -dependent exocytosis occurs, but when stimulated after a delay, this reaction is markedly reduced.…”
Section: Figurementioning
confidence: 99%
“…The effects on exocytosis were independent of changes on the cytoskeleton [7]. Independent studies using a different approach also identified Rac as an effector of exocytosis from these cells [8]. In none of these reports has the downstream component regulated by these G-proteins been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work has revealed several candidate G-proteins that are involved in exocytosis. These include the Rho family members Rac and Rho [6][7][8], and the heterotrimeric G-protein G i$ [9]. The constitutively active mutant proteins V14RhoA and V12Rac1 enhanced Ca# + -regulated exocytosis from permeabilized mast cells by increasing the proportion of cells that were competent to respond to stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased intracellular calcium [Ca 2ϩ ] i represents a ubiquitous second messenger system in cells, linking receptor activation to downstream signaling pathways. Previous studies (15)(16)(17)(18) have described relationships between intracellular calcium and the activation and function of Rho family GTPases in processes including muscle contraction and the exocytic response. Intracellular calcium is also required for thrombin-and collagen-induced Rac activation in platelets (19).…”
mentioning
confidence: 99%